Pengembangan Model Pembelajaran Sosiolinguistik Berbasis Lingkungan Melalui ADDIE Model pada PBS-FKIP Universitas Jambi - Andiopenta, Andiopenta (Universitas Nusantara PGRI Kediri, 2019)
This study aims to produce an environmental-based Sociolinguistic learning model. The research method used is ADDIE model development research with stage (1) analysis, stage (2) design, stage (3) development, stage (4) implementation, stage (5) evaluation, and stage (6) production. The results of product trials, both stage one tests showed an increase in the average of 6.1 to 8.01. In the second phase of testing too, from 4.61 increased to 5.94. These results illustrate that the teaching material produced is suitable for use. In the t-test of the product in the small group, the average score of 4.56 was seen, while in the post-test it showed an average of 4.74, and the t-count of 8,099 was still greater than the t-table of 2,132, so the difference was very significant. Likewise, in the large group test, the parates average was 7.84, while the average post-test was 8.50, and the t-test was 9.573, which was also still greater than the t-table 2.132, so the difference was very significant. Based on the results of the study, an environment-based sociolinguistic learning model produced from this study is feasible to use. Syllabus and sociolinguistic learning models based on the environment produced from this research are very in accordance with the needs of students of the Indonesian Language and Literature Education Study Program at the Faculty of Social Sciences, Jambi University in taking Sociolinguistics Courses.